ANALISIS SEMANTIK RAGAM MAKNA PADA LIRIK LAGU DESEMBER KARYA BAND EFEK RUMAH KACA - Marina Dwita Jannah (Universitas Sultan Ageng Tirtayasa, 2021)
Results Based on research and discussion on the analysis of the various meanings and messages contained in the song entitled December by the Efek Rumah Kaca band, it can be said that the song December contains six semantic meanings and has the deepest message that is stellar. The six types of meanings contained in the lyrics of the December song are lexical meaning, connotative meaning, referential meaning, non-referential meaning, associative meaning, and proverb meaning. In several types of meanings that have been discussed in the discussion, the connotative meaning is the meaning that is most commonly found in the lyrics of the December song, which is as many as four pieces of data. Other types of meanings include one data lexical meaning, one referential meaning, one non-referential meaning, two associative meanings, and the last meaning of proverbs is two pieces of data. The message contained is that we as living beings must always be grateful for whatever circumstances we do in our lives. Because with certainty and confidence, all the problems of our life pass quickly and believe that every day and pain there will always be happiness and a better life awaits in the future.